The Effects of Meditation and Visualization on the Direct Mental Influence of Random Event Generators - Collesso, Tayzia; Forrester, Maria; Baruss, Imants (Journal of Scientific Exploration, 2021)
Meditation and visualization exercises have been found to alter an individual’s mood and perception, and it is hypothesized that these techniques will enhance one’s ability to anomalously influence the function of a random event generator (REG) with the mind. This study is comprised of a control experiment and a second experiment with the administration of meditation and visualization exercises. There was no support for a significant deviation of the REG in the direction of the participants’ volition in Experiment 1, t(29) = -1.26, p = .22 (two-tailed), but results revealed a significant deviation in the intended direction in Experiment 2, t(29) = 2.66, p = .01 (two-tailed). Moreover, comparisons between cumulative deviations across both samples were found to be statistically significant, indicating that meditation and visualization exercises may promote significant deviations, t(58) = -2.69, p = .009 (two-tailed). These analyses suggest that the use of meditation and visualization techniques in experiments that study direct mental influence may be beneficial for finding anomalous effects. Keywords: meditation, visualization, random event generator, direct mental influence